2023
DOI: 10.14740/cr1458
|View full text |Cite
|
Sign up to set email alerts
|

Is T-Wave Alternans a Repolarization Abnormality Marker in COVID-19? An Investigation on the Potentialities of Portable Electrocardiogram Device

Abstract: Background: Cardiac arrhythmias are significantly associated with poor outcomes in coronavirus disease 2019 patients. Microvolt T-wave alternans (TWA) can be automatically quantified and has been recognized as a representation of repolarization heterogeneity and linked to arrhythmogenesis in various cardiovascular diseases. This study aimed to explore the correlation between microvolt TWA and COVID-19 pathology.Methods: Patients suspected of COVID-19 in Mohammad Hoesin General Hospital were consecutively eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Similar to LPs, TWA is particularly useful in predicting lethal ventricular arrhythmias and sudden cardiac death in patients with ischemic heart disease. Tondas et al reported that the TWA levels are elevated at discharge compared with those at admission in patients with COVID-19 [20]. HRV evaluates autonomic function based on variability in RR intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to LPs, TWA is particularly useful in predicting lethal ventricular arrhythmias and sudden cardiac death in patients with ischemic heart disease. Tondas et al reported that the TWA levels are elevated at discharge compared with those at admission in patients with COVID-19 [20]. HRV evaluates autonomic function based on variability in RR intervals.…”
Section: Discussionmentioning
confidence: 99%